Tracer-aided ecohydrological modelling across climate, land cover, and topographical gradients in the tropics - Arciniega Esparza, Saúl (2023)
Quantitative estimations of ecohydrological water partitioning into evaporation and transpiration remains mostly based on plot-scale investigations that use well-instru mented, small-scale experimental catchments in temperate regions. Here, we attempted to upscale and adapt the conceptual tracer-aided ecohydrology model STARRtropics to simulate water partitioning, tracer, and storage dynamics over daily time steps and a 1-km grid larger-scale (2565 km2) in a sparsely instrumented tropical catchment in Costa Rica. The model was driven by bias-corrected regional climate model outputs and was simultaneously calibrated against daily discharge observations from 2 to 30 years at four discharge gauging stations and a 1-year, monthly stream water isotope record of 46 streams. The overall model performance for the best dis charge simulations ranged in KGE values from 0.4 to 0.6 and correlation coefficients for streamflow isotopes from 0.3 to 0.45. More importantly, independent model derived transpiration estimates, point-scale residence time estimates, and measured groundwater isotopes showed reasonable model performance and simulated spatial and temporal patterns pointing towards an overall model realism at the catchment scale over reduced performance in the headwaters. The simulated catchment system was dominated by low-seasonality and high precipitation inputs and a marked topo graphical gradient. Climatic drivers overrode smaller, landcover-dependent transpira tion fluxes giving a seemingly homogeneous rainfall-runoff dominance likely related to model input bias of rainfall isotopes, oversimplistic Potential Evapotranspiration (PET) estimates and averaged Leaf Area Index (LAI). Topographic influences resulted in more dynamic water and tracer fluxes in the headwaters that averaged further downstream at aggregated catchment scales. Modelled headwaters showed greater storage capacity by nearly an order of magnitude compared to the lowlands, which also favoured slightly longer residence times (>250 days) compared to superficially well-connected groundwater contributing to shorter streamflow residence times (<150 days) in the lowlands. Our findings confirm that tracer-aided ecohydrological modelling, even in the data-scarce Tropics, can help gain a first, but crucial approxi mation of spatio-temporal dynamics of how water is partitioned, stored and transported beyond the experimental catchment scale of only a few km2.